Pengaruh Model Project Based Learning terhadap Hasil Belajar IPAS Siswa Kelas V Sekolah Dasar - Meila Noor Santi; Noviana Dini Rahmawati; Effendi Isnuryantono (Departement of Mathematics Education, 2024)
Science learning plays an important role in providing knowledge related to nature, living creatures and their environment. This learning is important to develop not only cognitive but also student skills. Teachers are expected to be able to innovate in designing learning that can provide real learning experiences for students. This research aims to determine the effect of the Project Based Learning model on the learning outcomes of science content content on getting to know the earth for class V SD N Gayamsari 02 Semarang. This research uses a quantitative approach to experimental methods with a one group pretest posttest design. Data collection techniques use test and non-test data, data are analyzed using quantitative methods. The research results show that there is an influence of implementing the Project Based Learning model on student learning outcomes with an N-Gain value of 0.63. This means that the application of the Project Based Learning model has an average increasing effect with moderate criteria on the science content learning outcomes of class V students at SD N Gayamsari 02 Semarang.